Characteristics of adverse drug reactions and their antidotes in a dental hospital in Bangkok, Thailand - Chaimanakarn, Sittipong; Rochanadumrongkul, Pichaya (Interdisciplinary Research Review, 2018)
The purpose of this descriptive study was to determine the characteristics of adverse drug reactions (ADRs) and to find out antidotes used to treat the patients that experienced adverse drug reactions in Outpatient department, Dental hospital. Data were collected from ADRs record document during the year of 2014 to 2016. Thirty two records were reported. Almost ADRs were cause from drug use in the hospital with the patients mean age 20-60. Together with the WHO Probability Assessment was mostly found in the scale of possible drug‐related (29% in 2014, 58% in 2015 and 38% in 2016). And the dermatology skin rash was the most ADRs reported Classification of type of reaction. The suspected drug was most commonly associated with Analgesic (37.5%). Followed with, both with antibiotics and analgesic (18.75%), antibiotic (9.38%), anesthetic (6.25%), and steroid (3.13%), were found respectively. And the most antidote drug that used to treat these patients was CPM (75.0 %), followed by CPM and Dexamethasone (15.63%), Ondansetron (9.38%), Dimenhydrinate (3.13%) and metoclopramide (3.13%). In conclusion, this study was required in order to determine the characteristics of ADRs data and antidote prescribed pattern in dental practice, which could be beneficial not only use as the trigger tools to finding out the more ADRs situation but also use this trigger for further development as standard ADRs reporting system in the hospital.